Hubungan Riwayat Pajanan Kromium Dengan Gangguan Fungsi Ginjal Pada Pekerja Pelapisan Logam di Kabupaten Tegal - Sudarsana, Eka; Setiani, Onny; Suhartono, Suhartono (Jurnal Kesehatan Lingkungan Indonesia, 2013)
Background : Chromium(Cr) metal coating industry potentially contaminate the working environment and surrounding community as result of Cr dust which would endanger health of the employees, because exposure of Cr (VI) especiallythroughaerosol inhalation may resulted disruption on respiratory effects, carcinogenic, liver and renals. According to data on cases of renal disease at dr. Soeseloregional hospital of Tegal regency in 2011, there were 256 patients of renal failure. Preliminary test on the waste water revealed that metal coatings industriescontaining Cr levels between 2,77 mg/l to 17,95 mg/1, sediment averagedby 20,32 mg/kg of maximum 25.46 mg/kg, and in the air of production room averaged by 1,5769 mg/m3 of maximum levels in the air by 1,8433 mg/m3, so the researchers interested for knowing the relationship between chromium exposure history and impaired renal function on metal coating workers in Tegal regency. Methods : The research method was an observational research with cross-sectional approach, with population of Cr coating industrial workers in Talang sub-district of Tegal regency. Sampling was using nonprobability samplingtechnique with purposive sampling by total sample of 30 people (total population) with examination on the Cr content in urine, creatinine, urea in the serum and interviews as supporting data. Result : Results showed that there were 15 people (50%) with impaired renal function, and there is relationship between chromium exposure with impaired renal function on workers with correlation coefficient of 0,783 p = 0.00 with significant increase, the higher chromium content in urine the higher creatinine levels in serum. Results of diagnostic test depicted the urine Cr contents may lead to impaired renal function so it's quite good to be used as a screening test. Conclusion: Cr contents in urine of workers of chromium metal coating ranged from 6.00 to 110,0 mg/l, serum creatinine levels ranged from 0.71 to 1,53 mg/dl, urea levels in serum ranged from 11,40 to 32,70 mg/dl. Logistics test on workers with high level of Cr content in urine will lead to impaired renal function 1,087 times higher than duration of works in Crmetal coating. Keyword: chromium, urinechromium, serum creatinine level, chromium metal coating,impaired renal function